2018
DOI: 10.1360/n092018-00153
|View full text |Cite
|
Sign up to set email alerts
|

Development of 4D printed shape memory polymers in biomedical field

Abstract: Development of shape memory polymers micro/nanofiber membranes in biomedical applicationsSCIENTIA SINICA Technologica 48, 811 (2018); 4D printing of personalized shape memory polymer vascular stents with negative Poisson's ratio structure: A preliminary study

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Wan et al (2020); Bai and Bu, 2022) assembled grasping mechanisms using the SMP prefabricated components prepared by laminating paper plates with SMP plates to achieve the function of grasping under external thermal excitation (Figure 2A). Li et al (2018) demonstrated a self-folding composite variable diameter wheel structure by 4D printing. This structure actuator consisted of a thermoplastic polyurethane elastomer (TPU) embedded in a polylactic acid (PLA) sandwich.…”
Section: Prefabricated Components Designed Based On Structural Combin...mentioning
confidence: 99%
See 2 more Smart Citations
“…Wan et al (2020); Bai and Bu, 2022) assembled grasping mechanisms using the SMP prefabricated components prepared by laminating paper plates with SMP plates to achieve the function of grasping under external thermal excitation (Figure 2A). Li et al (2018) demonstrated a self-folding composite variable diameter wheel structure by 4D printing. This structure actuator consisted of a thermoplastic polyurethane elastomer (TPU) embedded in a polylactic acid (PLA) sandwich.…”
Section: Prefabricated Components Designed Based On Structural Combin...mentioning
confidence: 99%
“…Through different printing methods combined with smart materials, prefabricated components with dynamic adaptability under predetermined structural excitation were developed, allowing for more creativity and freedom in the structure design of smart equipment, with numerous advantages over conventional manufacturing (Arif et al, 2022a).Shape memory polymers (SMP), an excitation-responsive smart material with shape memory properties, could change from a temporary shape to an initial shape in response to external excitation and complete a shape memory cycle (Khalid et al, 2021a). SMP was initially developed by the French company Cdf Chime and was a polynorbornene sheet (Li et al, 2018). SMP has shown great potential in many applications because of its lightweight, adjustable transition temperature, biocompatibility, distinguishable actuating mode, low cytotoxicity, and large deformation, compared with other smart materials, such as shape memory alloys and shape memory ceramics (Khalid et al, 2021b;Khalid et al, 2022b).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The research mainly focuses on direct ink writing based 4D printing [37], shape memory polymers based 4D Printing. The team uses 4D printing technology in a wide range of aerospace, aviation, and biomedical applications with excellent research results [21,[38][39][40]. At the same time, the above two teams cooperated in the development and application of metamaterials and photopolymerization technology in the field of 4D printing.…”
Section: Statistical Analysis Of Core Journalsmentioning
confidence: 99%
“…Furthermore, Leng combs the development direction and challenges in memory polymer composites around the application development trends. The applications of shape memory polymer composites in 4D printing are discussed in detail, including building materials, textiles, aerospace, electronics, medical equipment, robots, information, daily necessities, and other fields [21][22][23].…”
Section: Introductionmentioning
confidence: 99%